Dupuytren’s Disease: A Comparative Narrative Review of Current Treatment Modalities - Hatala, Patrycja; Grzywacz-Guza, Aleksandra; Kantor, Berenika; Gruba, Martyna; Bździuch , Patrycja; Cencelewicz , Katarzyna; Lewczuk , Aleksandra; Mozgała, Nikodem (Journal of Education, Health and Sport, 2026)
Background. Dupuytren’s contracture (DC) is a fibroproliferative disorder of the palmar fascia, characterized by progressive finger flexion deformities and impaired hand function. The condition has a multifactorial etiology, including genetic predisposition, metabolic factors (e.g., diabetes), and environmental factors such as microtrauma and occupational exposure. Its global prevalence is approximately 8%, highlighting the growing clinical need to optimize treatment strategies. The disorder is also frequently observed in athletes, particularly those engaged in sports involving repetitive hand use, such as field hockey. Objective. The aim of this narrative review is to provide a comprehensive synthesis of current evidence on the treatment of Dupuytren’s contracture (DD). The gathered data are intended to support clinical decision-making by comparing available therapeutic approaches. Material and methods. A narrative literature review was conducted using PubMed, covering studies published between 2016 and 2026. References in included articles were also screened. The analysis focused on comparing the effectiveness, recurrence, safety, and functional outcomes of surgical, minimally invasive, and non-surgical treatments. Results. Available evidence indicates that surgical treatment provides the most durable outcomes. Limited fasciectomy remains the reference standard in Dupuytren’s disease, offering the lowest recurrence rates, though it is associated with longer recovery and a higher risk of complications. Minimally invasive approaches enable faster recovery but are associated with higher recurrence rates. Non-surgical and emerging therapies currently lack robust supporting evidence. Conclusions. Treatment should be individualized, balancing effectiveness, recurrence risk, and recovery time. Further studies are needed to define the role of newer therapies and optimize management strategies